2021
DOI: 10.1038/s41598-021-90621-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different anesthesia modalities during percutaneous kyphoplasty of osteoporotic vertebral compression fractures

Abstract: Local and general anesthesia are the main techniques used during percutaneous kyphoplasty (PKP); however, both are associated with adverse reactions. Monitored anesthesia with dexmedetomidine may be the appropriate sedative and analgesic technique. Few studies have compared monitored anesthesia with other anesthesia modalities during PKP. Our aim was to determine whether monitored anesthesia is an effective alternative anesthetic approach for PKP. One hundred sixty-five patients undergoing PKP for osteoporotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Several studies have aimed to optimize the anesthesia technique used for PKP. Ge et al 10 found that anesthesia monitoring and dexmedetomidine use can result in better patient cooperation, a shorter duration of surgery, and a lower incidence of adverse events due to better sedation and analgesia than GA and LA. However, postoperative circulatory dysfunction can occur, and mean arterial pressure and heart rate should be closely observed and monitored postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have aimed to optimize the anesthesia technique used for PKP. Ge et al 10 found that anesthesia monitoring and dexmedetomidine use can result in better patient cooperation, a shorter duration of surgery, and a lower incidence of adverse events due to better sedation and analgesia than GA and LA. However, postoperative circulatory dysfunction can occur, and mean arterial pressure and heart rate should be closely observed and monitored postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, the high cost of PKP under GA should be considered when choosing the type of anesthesia. 10 Numerous studies have con rmed that the sinus nerve plays a major role in the innervation of the vertebral body, and local anesthetics act on the sinus nerve to produce analgesia. [14][15][16] We believe that LA with additional intravertebral anesthesia (IVA) can improve tolerance to surgery and avoid GArelated complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, MAC had the highest periprocedural satisfaction and lowest VAS 2 h after the procedure, with improved patient cooperation and a decreased risk of adverse events during PKP. The MAP and HR in the MAC group should be closely observed postprocedurally [47 ▪ ].…”
Section: Kyphoplastymentioning
confidence: 98%
“…The most common anaesthetic techniques used are general anaesthesia and local infi ltration anaesthesia, which can be combined with sedation/anxiolysis and monitored anaesthesia care (2,3).…”
Section: Technique Overviewmentioning
confidence: 99%